2002
DOI: 10.1063/1.1496128
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced flux pinning in Zr-doped MgB2 bulk superconductors prepared at ambient pressure

Abstract: We prepared a series of Mg 1Ϫx Zr x B 2 bulk samples with different x values by the solid-state reaction at ambient pressure and investigated the effects of the Zr doping on phase compositions, microstructure, and flux pinning behavior. The results indicate that the a axis increases with the increase of the Zr doping and the c axis remains unchanged. ZrB 2 phases form and a small amount of Zr atoms may substitute Mg in Zr-doped samples. Critical temperature drops with increasing the Zr doping. It is found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…Chemical doping is an effective method for introducing flux pinners in a superconductor. Various nanoparticles and materials such as C, diamond, SiC, SiO 2 , Ti, Zr, Fe, Ag, 10–17 and some organic compounds have been introduced in MgB 2 . These dopants improved the flux pinning and J c ( H ) of MgB 2 to different extents.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical doping is an effective method for introducing flux pinners in a superconductor. Various nanoparticles and materials such as C, diamond, SiC, SiO 2 , Ti, Zr, Fe, Ag, 10–17 and some organic compounds have been introduced in MgB 2 . These dopants improved the flux pinning and J c ( H ) of MgB 2 to different extents.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Zr-doping also offered the enhanced J c characteristics [17]. The optimal Ti-and Zr-doping level of 10% was found in the literatures [15,17,19]. Goto et al claimed that the Zr-and Hfdoping were more effective to enhance the J c -properties than the Ti-doping and obtained the maximized J c at the doping level of 1%-2% [18].…”
Section: Introductionmentioning
confidence: 98%
“…The pioneering work, which examined the Ti-doping effects, showed that the three orders magnitude larger J c was achieved for the Ti10%-doped MgB 2 sample compared to that of the non-doped one [15]. Furthermore, the Zr-doping also offered the enhanced J c characteristics [17]. The optimal Ti-and Zr-doping level of 10% was found in the literatures [15,17,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the chemical doping of secondary phases 12 or proton irradiation techniques 13 have been used to introduce flux pinning centers into MgB 2 to inhibit a rapid drop of the critical current density ( J c ) that occurred at high magnetic fields. In fact, it was reported that Zr‐doping achieved a high J c of 5.7 × 10 5 A/cm 2 at 5 K in a 2 T magnetic field because of the strong pinning effect 14 …”
Section: Introductionmentioning
confidence: 99%